MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MELALUI PENGGUNAAN PROJECT BASED LEARNING DALAM PEMBELAJARAN SAINS UNTUK ANAK USIA DINI - Pepi Mulyani, - (2022)
ABSTRACT Critical thinking skills need to be developed because it is one of the success factors in learning. However, the development of critical thinking in early childhood still requires stimulation and guidance related to children's curiosity in making concepts, analyzing, and making conclusions. The purpose of this study is to improve critical thinking skills through the use of Project Based Learning in science learning. This study involved 17 students and 2 PAUD teachers at TKN Pembina Cibaliung as subjects. This research uses mixed methods research which is a testing effort by uniting two types of qualitative and quantitative approaches in research. Researchers conduct classroom action research (CAR), which starts from planning, observing, and reflecting. Data was collected by using observation, interview, documentation and field notes. The findings obtained after the implementation of the Project Based Learning learning model have increased and it is proven that through the Project Based Learning learning model can improve critical abilities at an early age such as children's curiosity in making concepts, analyzing, and making conclusions. Based on the results of the study, the use of Project Based Learning through science learning can be used as an effective method for educators to improve children's critical thinking skills. Keywords: Critical Thinking, Project Based Learning